Diffractive Respondings and Cutting Together-Apart: Toward More-Than-Human Academic Community. (April 2023) - Thorpe, Holly; Newman, Joshua; Zarabadi, Shiva; Pavlidis, Adele; Fullagar, Simone; Rosiek, Jerry; Nichols, Erin; Markula, Pirkko; Bayley, Annouchka; Adkins-Cartee, Mary
In this "paper, " we share our process of exploring the possibilities for the emergence of new ways of knowing-thinking-doing response-able collaboration. In an effort to come "together-apart" as author-collaborators, working from our different positionings and locations in the world, we shared text and images of the various ways the ideas from individual papers (nodal points) and our diffractive processes were moving (with) us. Sharing these creative respondings, new relations co-emerged through the texts-images and the various diffractive patterns that traveled widely through screens, devices, bodies, from New Zealand and Australia, to Iran, London, Finland, Canada, and the West and East Coasts of the United States. Paying attention to the fine details, difference emerged, as did new forms of more-than-human connection. The visual and written respondings were then cut together-apart (literally, metaphorically and methodologically) to represent the multiplicities of the diffractive process, bodies, hauntings, absences and excess, and the tensions and affective vulnerabilities that co-emerged through our process. We present four visual montages of the diffractive patterns that surfaced from the individual papers as nodal points and our creative collaborative processes of becoming-with the special issue. We conclude with some final thoughts on the process of diffracting the special issue, inviting the reader to join us in imagining new lines of flight, alternative possibilities for becoming a more response-able, more-than-human academic community.